Reliability analysis on Selective Theory Sorter (STS) in Malaysia context: a preliminary study - Ghazali, Nor Mazlina; Wan Jaafar, Wan Marzuki; Ahmad Tarmizi, Rohani; Mokhtar, Halimatun Halaliah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Previous research is mentioned there is lacked of research in this area. However, a theoretical orientation is one of importance factor in determining the effectiveness of counseling or supervision process which contributed to the positive outcome. This preliminary study incorporated item analysis and reliability analysis of Selective Theory Sorter (STS) in Malaysian context. This instrument has been developed by Halbur and Halbur (2006). Preliminary study involved 31 students from Bachelor of Education (Guidance and Counseling) with Honor in public university in Malaysia who undergo the internship program in organizations. This instrument is measured twelve (12) types of theories which are psychoanalytic, Adlerian, Jungian, Person-Centered Therapy, Gestalt Therapy, Transactional Analysis, Behaviorism, Rational Emotive Behavior Therapy, Reality Therapy, Cognitive Behavioral Therapy, integrative, and existential. Item analysis mentioned there is high reliability on six (6) types of theories, three (3) stated on moderate and low reliability analysis. However, in overall the finding shows high reliability analysis at α = .94. Therefore, the value of reliability on each subscale were moderately reliable in measuring the theoretical orientation of university students, Psychoanalytic at α = .67, Adlerian at α = .44, Jungian at α = .74, Person – Centered Therapy at α = .63, Gestalt Therapy at α = .56, Transactional Analysis at α = .56, Behaviorism at α = .35, Rational Emotive Behavior Therapy at α = .45, Reality Therapy at α = .59, Cognitive Behavioral at α = .63, Integrative at α = .72 and Existential at α = .67. Implications of the findings for counselor, supervisor, trainee counselors and areas for future research are discussed.